Pemetaan Kompetensi Pengurus Barang Pengguna Barang Milik Daerah Pemerintah Provinsi Papua - Atmojo, Bambang Tri; Siswidiyanto, Sisiwidiyanto; Danar, Oscar Radyan (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
The quality of the asset administrator influences the quality of the financial reports of The Government of Papua. Based on the results of the BPK RI (Badan Pemeriksa Keuangan Republik Indonesia) review, the findings of asset management are related to the management procedures conducted by the asset administrator in The Government of Papua. The mapping of asset administrator competencies will provide an overview of asset administrator competence gaps and development needs. Competence mapping can be carried out using Permendagri No. 38/2017 concerning the Competence Standards for ASN Positions consisting of three types of competence, namely technical competence, managerial competence and socio-cultural competence. Technical competence refers to Permendagri No. 19/2016, which outlines out all the duties, functions and authorities of asset managers. Asset administrator competence mapping can assist the Government of Papua in the planning of future asset administrator competence development in order to optimize asset management performance. The diverse educational backgrounds of asset administrator and the lack of training lead to a wide range of educational and training needs that can be applied.